Studies at the grammar-discourse interface discourse markers and discourse-related grammatical phenomena - Haselow, Alexander; Hancil, Sylvie (Studies in language companion series ;, 2021)
"This book investigates phenomena at the grammar-discourse interface with a strong focus on discourse markers, whose development and concrete uses in a given language tend to be based on a close interplay of grammatical and discourse-related forces. The topics range from the transition of linguistic signs "out of" sentence grammar and "into" the domain of discourse to differences between more grammatical vs. more discourse-pragmatic expressions in terms of structural behavior and cognitive processing, and the different, intricate ways in which the usage conditions and meanings of grammatical constituents or structural units are affected by the discourse context in which they are used. The twelve studies in this book are based on fresh empirical data from languages such as English, Basque, Korean, Japanese and French and involve the study of linguistic expressions and structures such as pragmatic markers and particles, comment clauses, expletives, adverbial connectors, and expressives"--